The Duke Conference on Doping in Sport (1999)
Jerry Diehl, National Federation of State High School Associations: The Significance of Leadership from Above Gary I. Wadler, M.D., Women's Sports Foundation: Doping in Sport: From Strychnine to Genetic Enhancement, It's a Moving Target Alberto Salazar, Marathoner and Coach: Locating the Line between Acceptable Performance Enhancement and Cheating Professor John Hoberman, The University of Texas at Austin: Learning from the Past: The Need for Independent Doping Control Philip Milburn, COO, USA Cycling, Inc., USOC Task Force on Doping: The Form and Substance of Independence: An Insider's View Craig A. Masback, CEO/USA Track & Field: Leadership from the Trenches Professor Paul H. Haagen, Duke Law School: The Court of Arbitration for Sport as a Model for Dispute Resolution